2020
DOI: 10.1051/0004-6361/202038740
|View full text |Cite
|
Sign up to set email alerts
|

Bar resonances and low angular momentum moving groups in the Galaxy revealed by their stellar ages

Abstract: We use the second Gaia data release to dissect the Milky Way disc in phase-space and relative ages. We confirm and report the existence of multiple velocity moving groups at low azimuthal velocities and angular momenta, below Arcturus, regularly separated by ∼18−20 km s−1 in azimuthal velocity. Such features were predicted to exist more than ten years ago, based on the reaction of the Milky Way to a perturbation in the disc undergoing phase-mixing. These structures appear slightly younger than their phase-spac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…the higher the fraction of stars in substructures. On the other hand, we do not have enough stars in the lower V * φ region in any of the populations to notice the low angular momentum ridges suggested in Laporte et al (2020b).…”
Section: Small Scale Velocity Structuresmentioning
confidence: 58%
“…the higher the fraction of stars in substructures. On the other hand, we do not have enough stars in the lower V * φ region in any of the populations to notice the low angular momentum ridges suggested in Laporte et al (2020b).…”
Section: Small Scale Velocity Structuresmentioning
confidence: 58%
“…This is particularly important in the context of the interpretation of recent data from the Gaia mission (Gaia Collaboration 2018a, 2021), which revealed in exquisite detail the fine structure of stellar action space (e.g., Trick et al 2019;Monari et al 2019a,b). While the existence of moving groups of dynami-cal origin had been known for a long time in local velocity space around the Sun (e.g., Dehnen 1998;Famaey et al 2005), Gaia revealed their structure in exquisite detail (Ramos et al 2018) and also provided an estimate of their age distribution (Laporte et al 2020), together with the shape of the global velocity field away from the Sun within the Galactic disc (Gaia Collaboration 2018b). One additional major finding of Gaia is the existence of a local phase-spiral in vertical height versus vertical velocity in the solar neighbourhood (Antoja et al 2018), which might be related to a vertical perturbation of the disc, for example by the Sagittarius dwarf galaxy (e.g., Laporte et al 2019;Binney & Schönrich 2018;Bland-Hawthorn & Tepper-García 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A crucial observable allowing to disentangle the various proposed scenarios is the shape of this phase-spiral as a function of stellar ages (e.g., [7]), which Chronos will provide. Moreover, the current structure of the Galactic bar itself is also constrained from Gaia data on disc kinematics in the Solar vicinity (e.g., [9]), but again, the dynamical effects of non-axisymmetric perturbations on stellar populations of various ages would allow to disentangle better the effect of the bar and spiral arms [8], and also to constrain the age of the Galactic bar itself, which is still largely unknown.…”
Section: Specific Observational Constraintsmentioning
confidence: 99%
“…They reveal unexpected trends, suggesting for instance that a large fraction of the oldest stars in the Galaxy have "disky" orbits [3], that the stellar halo is almost fully accreted (e.g., [4]) and that these accreted components in turn played an important role in shaping the in-situ "disky" components (e.g., [5]), while it appears that more recent accretions are still influencing disc dynamics today [6,7]. The respective roles of such external perturbations and internal instabilities such as the Galactic bar, the structure of which is also being constrained with Gaia (e.g., [8,9]), and the interplay between these external and internal dynamical mechanisms, are however still under investigation. To reach a more precise view of the situation, it is essential to enrich the very precise astrometric-kinematic-chemical view of the Galaxy provided by Gaia and large spectroscopic surveys with high precision ages which can be provided through seismic information (or more generally time domain information).…”
mentioning
confidence: 99%